BIRD ACCOUNTING: A CRITICAL REVIEW OF THE VALUATION OF BIOLOGICAL ASSETS - Yusdita, Elana Era; Riestanty, Anggie; Tantama, Ardiyanto Darma (FIPA : Forum Ilmiah Pendidikan Akuntansi, 2022)
This study aims to determine the application of accounting to breeders and bird traders as well as to bring up the values of local wisdom which have been lost in standardized financial reports. To answer this goal, the methodology used is critical phenomenology. It turns out that there are social and spiritual aspects that shape the value of a biological asset in addition to the economic aspect. With financial accounting in the form of bird accounting, breeders and biological asset traders can assess their assets based on costs to reflect their owners' love for their pets and their performance records and other qualitative information to reflect their asset value. Biological assets cannot be equated with fixed assets because life cannot be depreciated by humans. The results of this study complement the critics of IAS in agriculture as a fellow biological assets as well as being a criticism of the concept of business unity.